Protective Effects of Curcumin on the Structural Parameters of Seminiferous Tubules and Leydig Cells in Methandienone Treated Mice - Omid Baharan; Nader Goodarzi* (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Although anabolic androgenic steroids (AAS) use has become became more prominent in bodybuilders and professional athletes, their consumption is nowadays a problem that involves a wider population. Methandienone or dianabol is an anabolic androgenic steroid which is used by athletes for fitness. This study was conducted to investigate, the likely protective effects of curcumin on the structural parameters of the testis in dianabol treated mice. Methods: A total of 35 male mice were divided into five groups, each containing seven mice. The control group received 0.2 mL distilled water; the second group received 20 mg/kg/day dianabol; third, fourth, and fifth groups received dianabol plus 50, 100, and 200 mg/kg/day of curcumin, respectively. All administrations were done by gavages for 56 days. On the last day, the left testes were examined using stereological methods. The volume of testis and seminiferous tubules, interstitial tissue, and diameter, length and germinal epithelium height of the tubules as well as the number of Leydig cells were estimated. Results:  The obtained results showed that the weight and volume of the testis as well as volume of the seminiferous tubules and interstitial tissue, length, diameter and epithelium height of the tubules decreased significantly (p<0.05) after dianabol administration compared to the negative control group. Oral administration of curcumin at doses 100 and 200 mg/kg, could significantly improve all the measured parameters toward the normal levels. Conclusion: It seems that curcumin due to its anti-oxidant and anti-inflammatory properties can inhibit testis volume reduction and hypogonadism following dianabol administration.